2010
DOI: 10.1177/0269215509343234
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for treatment of attention deficits after non-progressive acquired brain injury. A systematic review

Abstract: Although there is lack of robust evidence to recommend the routine use of medication to improve attention after traumatic brain injury and stroke, the existing evidence indicates potential for benefit in some patents and therefore further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…More recently, some investigators have suggested that SPECT imaging could even assist clinicians in developing treatment strategies. For example, decreased prefrontal cortex perfusion, which can be associated with executive dysfunction arguably may be helped with psychostimulants [23], [24] or other interventions to enhance the function of the frontal lobes. Temporal lobe hypoperfusion has been associated with irritability and mood instability that may be improved with anticonvulsant or antidepressant medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, some investigators have suggested that SPECT imaging could even assist clinicians in developing treatment strategies. For example, decreased prefrontal cortex perfusion, which can be associated with executive dysfunction arguably may be helped with psychostimulants [23], [24] or other interventions to enhance the function of the frontal lobes. Temporal lobe hypoperfusion has been associated with irritability and mood instability that may be improved with anticonvulsant or antidepressant medication.…”
Section: Introductionmentioning
confidence: 99%
“…Another line of evidence regarding the dopaminergic effect of TBI is that dopamine receptor agonists often benefit patients via the promotion of central dopaminergic transmission [23], [24]. This could be a sign that dopamine release is suppressed after injury, that dopamine uptake by the DAT is increased, or some combination of the two.…”
Section: Introductionmentioning
confidence: 99%
“…13,22,23,58–65 There is evidence, including randomized controlled trials, to support the use of methylphenidate in the setting of traumatic brain injury. 13,22,5860,66 It is recommended to treat deficits in attention and speed of processing, and as an option for treating deficiencies in general cognitive functioning. 51 …”
Section: Cognitivementioning
confidence: 99%
“…A recent study (Gorgoraptis et al, 2012) found that the administration of rotigotine improved performance on the cancellation task, and another found that treatment with carbidopa-levodopa significantly improved BIT scores in three of four patients (Mukand et al, 2001). Although the results appear promising, other studies have not replicated these findings (Buxbaum et al, 2007), highlighting the need for further clinical trials (Sivan et al, 2010). The efficacy of pharmacological interventions in neglect is also often hampered by patients' lack of insight, self-monitoring and motivation, all of which lower compliance.…”
Section: Anatomymentioning
confidence: 99%